1993
DOI: 10.9746/sicetr1965.29.1337
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Electro-Pneumatic Positioner Valve System Considering Non-Linear Characteristics of Pilot Valve

Abstract: Control valves play very important role as final control elements in process control system and most of them are driven by the pneumatic pilot valve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Its seriousness is determined by the friction characteristics. Detailed analysis of this phenomenon can be seen in the past studies [13,14].…”
Section: Description Of Stick-slip Faultmentioning
confidence: 99%
“…Its seriousness is determined by the friction characteristics. Detailed analysis of this phenomenon can be seen in the past studies [13,14].…”
Section: Description Of Stick-slip Faultmentioning
confidence: 99%
“…Its seriousness is determined by the friction characteristics. Detailed analysis of this phenomenon can be seen in the past studies (Li C.B., 1982;Kagawa et al 1993). Fig.…”
Section: Ty"ical Malfuncti"ns "F Digital ""Siti"nersmentioning
confidence: 99%
“…The structure of the pilot valve is complex. Literature [1] has presented the dynamic characteristics of the pneumatic diaphragm motor with a conventional positioner. Experimental fi ndings demonstrated that when the speed of the process fl uid becomes large the actuator tend to oscillatem, and it is necessary to make efforts to improve the stiffness of the diaphragm motor in order to satisfy the needs of the development of the process plant131.…”
mentioning
confidence: 99%